Levelized cost of energy (LCOE) metric to characterize solar absorber coatings for the CSP industry. (January 2016) - Boubault, Antoine; Ho, Clifford K.; Hall, Aaron; Lambert, Timothy N.; Ambrosini, Andrea
Abstract: The contribution of each component of a power generation plant to the levelized cost of energy (LCOE) can be estimated and used to increase the power output while reducing system operation and maintenance costs. The LCOE is used in order to quantify solar receiver coating influence on the LCOE of solar power towers. Two new parameters are introduced: the absolute levelized cost of coating (LCOC) and the LCOC efficiency. Depending on the material properties, aging, costs, and temperature, the absolute LCOC enables quantifying the cost-effectiveness of absorber coatings, as well as finding optimal operating conditions. The absolute LCOC is investigated for different hypothetic coatings and is demonstrated on Pyromark 2500 paint. Results show that absorber coatings yield lower LCOE values in most cases, even at significant costs. Optimal reapplication intervals range from one to five years. At receiver temperatures greater than 700 °C, non-selective coatings are not always worthwhile while durable selective coatings consistently reduce the LCOE—up to 12% of the value obtained for an uncoated receiver. The absolute LCOC is a powerful tool to characterize and compare different coatings, not only considering their initial efficiencies but also including their durability. Highlights: Optimal coating reapplication intervals that minimize the LCOE exist. Absolute LCOC shows higher sensitivity to the coating degradation than to its cost. Selective coatings represent considerable LCOE reductions at high temperatures. Current and future absolute LCOCs of Pyromark 2500 are estimated. Receiver coatings could reduce the LCOE by up to 12%.